2017
DOI: 10.1016/j.jneuroling.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism influences structural indices of interhemispheric organization

Abstract: Bilingualism represents an interesting model of possible experience-dependent alterations in brain structure. The current study examines whether interhemispheric adaptations in brain structure are associated with bilingualism. Corpus callosum volume and cortical thickness asymmetry across 13 regions of interest (selected to include critical language and bilingual cognitive control areas) were measured in a sample of Spanish-English bilinguals and age- and gender-matched monolingual individuals (N = 39 per grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 88 publications
3
35
0
Order By: Relevance
“…Contrary to our first hypothesis, we found reductions in FA and increases in MD of fiber tracts implicated in EF in bilingual patients with TLE relative to the HC groups and monolingual patients with TLE. Greater WM integrity has been reported in bilingual healthy adults, children, and older adults; this could represent greater available neural substrates. The changes in WM structure in bilingual subjects have been proposed to lead to more widely distributed cognitive networks, resulting in more efficient communication between brain regions.…”
Section: Discussionmentioning
confidence: 90%
“…Contrary to our first hypothesis, we found reductions in FA and increases in MD of fiber tracts implicated in EF in bilingual patients with TLE relative to the HC groups and monolingual patients with TLE. Greater WM integrity has been reported in bilingual healthy adults, children, and older adults; this could represent greater available neural substrates. The changes in WM structure in bilingual subjects have been proposed to lead to more widely distributed cognitive networks, resulting in more efficient communication between brain regions.…”
Section: Discussionmentioning
confidence: 90%
“…Felton et al . found similar results in young adults . They examined the corpus callosum and found that bilinguals had greater volume in the middle‐anterior and central regions than monolinguals.…”
Section: Greater Integrity Of White Matter Structures For Bilingualsmentioning
confidence: 99%
“…Structural magnetic resonance imaging (MRI) has revealed that young adult bilinguals have greater white matter volume than their monolingual peers. These differences are particularly reliable in the corpus callosum, and may allow bilinguals to exchange cross-hemispheric information more efficiently than monolinguals (e.g., Coggins et al, 2004; Felton et al, 2017). …”
Section: Introductionmentioning
confidence: 99%